2014
DOI: 10.1038/leu.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of acute myeloid leukemia in vitro and in vivo with an anti-CD123 mAb engineered for optimal ADCC

Abstract: Acute myeloid leukemia (AML) is a biologically heterogeneous group of related diseases in urgent need of better therapeutic options. Despite this heterogeneity, overexpression of the interleukin (IL)-3 receptor α-chain (IL-3 Rα/CD123) on both the blast and leukemic stem cell (LSC) populations is a common occurrence, a finding that has generated wide interest in devising new therapeutic approaches that target CD123 in AML patients. We report here the development of CSL362, a monoclonal antibody to CD123 that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 48 publications
4
117
0
Order By: Relevance
“…A loose correlation between these two properties was observed for bulk AML cells (Figure 3), and similar correlations have been reported for the CD33-specific BiTE AMG330, 9 the CD123 antibody Talacotuzumab (CSL 362), 48,49 and the CD3 x CD123 DART agent MGD006. 56 While the target antigen density likely dictates the strength of binding of these agents to the target cells and the subsequent engagement of killer cells, it is unlikely that binding strength alone will translate 1:1 into an enhanced lytic activity.…”
Section: Discussionsupporting
confidence: 81%
“…A loose correlation between these two properties was observed for bulk AML cells (Figure 3), and similar correlations have been reported for the CD33-specific BiTE AMG330, 9 the CD123 antibody Talacotuzumab (CSL 362), 48,49 and the CD3 x CD123 DART agent MGD006. 56 While the target antigen density likely dictates the strength of binding of these agents to the target cells and the subsequent engagement of killer cells, it is unlikely that binding strength alone will translate 1:1 into an enhanced lytic activity.…”
Section: Discussionsupporting
confidence: 81%
“…Recently, there have been increasing efforts to identify molecular aberrations that could serve as pharmacologic targets within AML and MDS stem cell compartments. [10][11][12][13][14][15][16] Resulting therapies have shown promising effects in preclinical studies, 17,18 but further work will be necessary to identify therapeutic targets against preleukemic stem cells that would lead to long-term remission and prevention of relapse in AML and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…IFN␥-mediated CD38 Up-regulation Requires p38, NF-B, and JAK/STAT-Previous studies have shown increased expression of CD38 by IFN␥ in chronic lymphocytic leukemia to be JAK/STAT and T-bet-dependent (20). To determine which downstream signaling pathways were required for the up-regulation of CD38 seen with IFN␥ treatment, primary AML apheresis samples were pretreated with inhibitors for ERK, PI3K, p38 MAPK, JAK/STAT, and NF-B.…”
Section: Ifn␥ Increases Fc␥ri Expression and Phagocytic Ability Inmentioning
confidence: 99%
“…The targeting of Fc␥RI has similarly been proposed, especially after the finding that IFN␥ could increase the expression of the high affinity Fc␥ receptor, Fc␥RI (16 -19). Recently, a study was completed using a monoclonal antibody to CD123 that has been humanized, affinity-matured, and Fc-engineered for increased affinity toward CD16 (Fc␥RIIIa), which showed an effect against AML both in vitro and in vivo in an environment with adequate NK cell function (20).…”
mentioning
confidence: 99%